Record Disaster Management in Local Government: A Case Study of Nyakagyeme Sub-County Rukungiri District. - Kayesu, Carolyne (Kabale University, 2024)
This research was on the topic entitled "Record Disaster Management in Local Government: A Case Study of Nyakagyeme Sub County, Rukungiri District. The study was guided by specific objectives which included; identifying records stored in the Nyakagyeme central Registry, examining constraints to the preservation of records, and identifying strategies for the effective preservation of records in local Government. Literature was reviewed based on the objectives of the study. A qualitative case study research design was used. The sample size consisted total of 07 respondents of whom five (5)were Sub County administrators and two (2) records officers. Data was collected using the Interviewing method and observation. The study findings indicated that the Registry stored; minutes of meetings, Reports, Policies and manuals, Circulars and mernos, and Financial records. Challenges record officers face in preserving records in the Nyakagyeme Central registry include; employing untrained personnel, unauthorized access to records, limited supervision, computer viruses and insect attacks, and limited training. The strategies for effective preservation of records in local Government included; the use of trained personnel, strengthening security through changing passwords, direct supervision by the supervisors, creating a backup system for records, organizing workshops to provide all records officers knowledge in record keeping, and restricting access to untrusted users. In conclusion, many records are created at Nyakagyeme Subcounty Rukungiri district but are not managed well. The local government should empower record officers with more skills to strengthen security in the local government registry by using passwords and biometric features of identification. The study recommends that there is a need for the management to enhance career progression by facilitating staff to go for further training in records management. To check on the challenges that hinder efficient management or records in the local government. the organization needs to enhance proper filing in the registry and provide filing skills to the employees. This can be done through electronic filing systems, the use of Movement Registers in case of power outages, conducting periodic census of records, regular staff training, and awareness of records management.